2022
DOI: 10.1111/cns.13880
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the role of Epac1‐SOCS3 signaling in the development of neonatal‐CRD‐induced visceral hypersensitivity in rats

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In addition, CRH is a key regulatory peptide mediating the hypothalamic-autonomic nervous system pathway to various stress responses and plays an important role in the stress response. Changes in intestinal motility were mainly related to the central role of CRH ( 8 ). Mönnikes et al ( 11 ) found that the neuroanatomical site of CRH-mediated changes in intestinal motility was in the PVN.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CRH is a key regulatory peptide mediating the hypothalamic-autonomic nervous system pathway to various stress responses and plays an important role in the stress response. Changes in intestinal motility were mainly related to the central role of CRH ( 8 ). Mönnikes et al ( 11 ) found that the neuroanatomical site of CRH-mediated changes in intestinal motility was in the PVN.…”
Section: Discussionmentioning
confidence: 99%
“…Further exploration of the cellular and molecular mechanisms of latent sensitization will help to deepen the understanding of chronic pain [ 60 ]. Studies have shown that EPAC is implicated in pain sensitization after inflammation or injury [ [61] , [62] , [63] ]. The neuropeptide tyrosine (NPY) and NPY Y1 receptor (Y1R) signaling cascade (called the NPY-Y1R axis) has an endogenous inhibitory effect on latent sensitization, and activation of this pathway can maintain pain relief.…”
Section: Epac1 Is Involved In Chronic Painmentioning
confidence: 99%
“…The incidence of IBS has been increasing in recent years, 4 whereas the etiology of IBS is not completely understood, which prevents effective treatments and thus makes a negative impact on the physiological and psychological well‐being of affected individuals 5,6 and increases the burden of the health care system. Currently, most research on chronic colorectal visceral pain focuses on the peripheral aspects, with limited research addressing the contribution of the central nervous system 7–11 . Therefore, exploring the regulatory mechanisms of the central nervous system on IBS colorectal visceral pain may promote understanding of IBS pathogenesis and identifying new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, most research on chronic colorectal visceral pain focuses on the peripheral aspects, with limited research addressing the contribution of the central nervous system. 7 , 8 , 9 , 10 , 11 Therefore, exploring the regulatory mechanisms of the central nervous system on IBS colorectal visceral pain may promote understanding of IBS pathogenesis and identifying new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%